Formulasi dan Uji Mutu Fisik Sediaan Losion Kombinasi Infusa Daun Kelor (Moringa oleifera Lam.) dan Bunga Telang (Clitoria ternatea L.) - Novita Silalahi; Annie Rahmatillah; Rahmat Hidayat (Journal of Innovative and Creativity, 2026)
ABSTRACT Moringa leaves (Moringa oleifera Lam.) and butterfly pea flowers (Clitoria ternatea L.) contain flavonoid compounds that act as natural antioxidants capable of scavenging free radicals. This study aimed to formulate a lotion preparation containing a combination of moringa leaf and butterfly pea flower infusions and to evaluate the physical quality of the resulting formulation. Four lotion formulas were prepared, consisting of F0 as a positive control and F1–F3 with variations in the ratio of moringa leaf and butterfly pea flower infusions, namely F1 (2:2), F2 (3:1), and F3 (1:3). Physical quality evaluation included organoleptic test, pH measurement, spreadability, adhesiveness, viscosity, globule size, and centrifugation test. The results showed that all lotion formulas exhibited physical characteristics that met the quality requirements for topical preparations. Organoleptic evaluation indicated that F0 was white, F1 was bluish-green, F2 was green, and F3 was blue in color, with lotion form and strawberry odor. The pH values were 6.26 for F0, 6.37 for F1, 6.63 for F2, and 6.52 for F3. Spreadability ranged from 5–7 cm, adhesiveness was more than 4 seconds, and the average viscosity values were 4,024 cPs for F0, 2,124 cPs for F1, 2,921 cPs for F2, and 2,669 cPs for F3. The globule size was small and uniform, and the centrifugation test showed no phase separation. Keywords: Butterfly Pea Flowers, Moringa Leaves, Skin, Lotion, Physical Quality